MENINGKATKAN KETERAMPILAN MENJAHIT BORDIR MELALUI LAYANAN PEMBELAJARAN INDIVIDUAL BAGI ANAK TUNARUNGU - Fahmi, Ardisal, Irdamurni (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was motivated by a deaf child who is less skilled in embroidery sewing. From the observations in the form of initial assessment clearly seen that the results are not neat and embroidered good kid, the kid looks just sew the edge of one of many steps in sewing, not movement foot and hand sew the child in making the seams look untidy and resulted in a broken sewing needle. Moreover, the formation of flowers, the child looks stiff in processing the flowers so that it looks unattractive, but because the child has received training and a little stock of MOSA in embroidery sewing. The purpose of this research is to improve the skills of embroidery sewing SLB YPPLB deaf children in Padang. Here researchers provide service learning individually about embroidery sewing skills with mastery of basic techniques, namely: suji straight sewing techniques, sewing techniques curved suji, suji circular sewing techniques and provide ornate embroidery on clothing. This type of research is the design of Single Subject Research AB. Data were collected by direct observation and recorded on the observation sheet. Data were analyzed using visual analysis of the graph which consists of the analysis and the analysis of the condition among the conditions. The results showed length is five times the baseline conditions of observation. The length of the intervention conditions ten times. Tendency toward baseline data demonstrated the ability of tailoring embroidery little boy up (+), whereas in the treatment condition showed the data embroidery sewing children's ability to increase again (+). In the baseline condition of the child's ability level changes stitch embroidery is (+17) capability, for the treatment of rate of change is (+67) capabilities. Analysis results between conditions showed: The number of variables that changed is that embroidery sewing skills, the overlap percentage is 0% means that there is an increase in the ability of ATR X stitch embroidery through individualized learning services in SLB YPPLB Padang.